Vaccination: potential adverse effects and future challenges - Aziz, Jazli; Rahman, Mohammad Tariqur (Kulliyyah of Science, IIUM, 2011)
Concerns over potential adverse effects of vaccination have been raised with the aim to develop and design efficient yet harmless vaccines. Using data derived from the reported vaccine efficiency trials and related research, we have analyzed the possible changes in homeostasis of the haematopoietic system in terms of level of antibody (Ab) after vaccination. Several vaccines were reported to increase a wide range of total Ab concentration such as <0.01%-2.40% in children and 0.02%-1.65% in adults. Reported increased level of IgG against Haemophilus influenza type-B was recorded as 605-1210 folds higher in children and 1226-2453 folds higher in adults than the required protective levels. Similar changes were also observed for other vaccines. Such increased level of total Abs at least theoretically can contribute to higher concentration of protein i.e., hyperproteinemia in blood. Since Ab is a polymer of amino acids; therefore hyperproteinemia due to increased level of Ab may in turn affect pH and osmosis of the blood. Therefore, an optimum dose of vaccine(s) for sufficient boost of immune mechanisms, rather than a dose required for highest efficiency, is recommended before an individual is vaccinated.